Effect of work activity on students’ learning motives at schools for working youth - Jakavičius, V. (Psichologija, 1962)
One or other motives, being the main stimulus in multifaceted human activities, also play an important role when attending school. The research by Soviet psychologists demonstrated that a student learning is stimulated by twofold motives at general education schools – directly incentive and indirectly sense-bearing; the content of one or other motives essentially consists of a student’s endeavor to prepare for life and take a particular place in the socialist society, as well as interest in one or another educational subject. Our research demonstrated that students at schools for working youth differ in the majority of cases in terms of learning motives from students of the larger general education schools. The main factor forming student learning motives at schools for working youth is their daily work in different sectors of the national economy. As a result of work, both direct incentive and indirect sense-bearing learning motives of students at schools for working youth are broader content-wise as compared with those at mass schools. If students at mass schools most often understand the necessity of knowledge as a condition to ensure their future, students at schools for working youth see it already today, in their daily work. The majority of this type of students seek knowledge because they understand that this is the only one condition enabling them to master contemporary sophisticated technique and technology processes. Thus, apart from the motives which are common to students of both type schools, the most important motives of students at schools for working youth is the perception that knowledge is necessary for successful work. In our opinion, here lies the main difference between the learning motives of students at schools for working youth and those at larger general education schools. However, when investigating learning motives of students at schools for working youth some diversity has been noticed. The following groups of students may be distinguished. a) Working students have essentially made up their minds about their place in life and have one or other goal. The essence of content of learning motives of these students lies in the knowledge being necessary for them in their direct work and for attaining the goal set. b) Students for whom knowledge is necessary for further studies. Unlike the first group students, the latter do not feel a huge impact of work that directly prompts their learning motives; this group mostly consists of students who come to school for working youth willing to acquire a job record necessary for entering a higher education school. c) Students forming a relatively small group who do not have clearly formulated learning motives.